Exploring Mental Health and Academic Outcomes of Children Receiving Non-manualized, Transdiagnostic, Task-Shifted Mental Health Care From Their Teachers in a Low-and-Middle Income Country - Vanderburg, Juliana L.; Dukpa, Choden; Rauniyar, Abhishek K.; Giri, Priscilla; Bhattarai, Surekha; Thapa, Arpana; Gaynes, Bradley N.; Hampanda, Karen; Lamb, Molly M.; Matergia, Michael; Cruz, Christina M. (Frontiers in Pediatrics, 2022)
A majority of children worldwide who face mental health difficulties, especially in low-and-middle income countries, remain undiagnosed and untreated. This deficit roots in part from a lack of trained professionals qualified to provide care. Task-shifting the provision of treatment to teachers, individuals with consistent access to children, can reduce the care gap. The current study investigated whether the implementation of a pilot trial of Tealeaf-Mansik Swastha (Teachers Leading the Frontlines – Mental Health; “Tealeaf”) was associated with improvements in child mental health and academic outcomes. Tealeaf is a transdiagnostic, non-manualized, task-shifting intervention in which teachers identify students in need of mental health care and then provide task-shifted care for them using an emerging, novel therapy modality, “education as mental health therapy” (Ed-MH). Pre-post standardized quantitative measures focused on child mental health status and academics. The measures were completed by multiple raters and compared to determine whether changes occurred. Results indicated that primary teacher raters observed significant improvements in child mental health symptoms overall, while secondary teacher raters and caregivers noted improvement for certain diagnostic categories. Caregivers observed on average a decreased impact of their children’s mental health symptoms on their children’s lives. Academically, math scores significantly improved while reading trended towards significance. Preliminary evidence overall supports the viability of Tealeaf and Ed-MH for positively impacting child mental health and academics. Future directions include the implementation of a formalized, randomized-controlled trial to strengthen preliminary outcomes.